Penilaian Tingkat Kesehatan Keuangan Badan Usaha Kredit Pedesaan (BUKP) Di Kabupaten Sleman - Ferdiansyah Rizki Fakhrurozi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research aims to determine the level of financial health of Rural Credit Business Entities (BUKP) in Sleman Regency. As well as to find out what obstacles and barriers exist in Rural Credit Business Entities (BUKP) in Sleman Regency. This research applies descriptive qualitative research methods, where the source of research data comes from the Regional Secretariat of Sleman Regency. Data sources used in this research include primary data and secondary data. Research data includes the results of interviews, observations and document reviews, as well as information from previous researchers which is used as a theoretical reference. The results of this research show efforts to increase the health level of BUKP in 17 sub-districts in Sleman Regency. Through calculations carried out on the aspects of NPL, LDR, RTA, RTE, NIM, BOPO and CAR, results can be found on the level of financial health of Rural Credit Enterprises (BUKP) in 17 sub-districts in Sleman Regency. In particular, for academics who study the criteria for assessing the level of financial health of BUKP, it is hoped that this research can serve as a comparison and at the same time a reference in exploring this problem. The agencies that host research may vary, but the basis and framework of this research can help researchers who wish to conduct similar research to explore various issues related to the criteria for assessing the level of financial health of BUKP.